Ultrafast transfer and transient entrapment of photoexcited Mg Electron in MgC60 - Madjet, Mohamed El-Amine; Ali, Esam; Carignano, Marcelo; Vendrell, Oriol; Chakraborty, Himadri S. (Physical review letters, 2021)
Electron relaxation is studied in endofullerene MgC60 after an initial localized photoexcitation in Mg by nonadiabatic molecular dynamics simulations. Two approaches to the electronic structure of the excited electronic states are used: (i) an independent particle approximation based on a density-functional theory description of molecular orbitals and (ii) a configuration-interaction description of the many-body effects. Both methods exhibit similar relaxation times, leading to an ultrafast decay and charge transfer from Mg to C60 within tens of femtoseconds. Method (i) further elicits a transient trap of the transferred electron that can delay the electron-hole recombination. Results shall motivate experiments to probe these ultrafast processes by two-photon transient absorption or photoelectron spectroscopy in gas phase, in solution, or as thin films.